PERCEPCIÓN Y EVALUACIÓN SOBRE LOS SERVICIOS SOCIALES. EL PATRONATO NACIONAL DE LA INFANCIA REVISIÓN DE LITERATURA - Jiménez Aguilar, Melissa (2012)
In research, the appreciation that people have about social services they receive is a great unknown. This study sought to review existing literature on perception and evaluation of social services in the central canton of Limon and in particular on social services provided by the National Foundation for Children (PANI in spanish). After a literature review no were found studies for the area of Limon on the topics of social services, PANI and evaluation of social services. However, after a narrative review of the national and international studies, it was found that these services need of modernization and continuous assessment to provide a response to current needs and changes that have the people targeted by the social good. So, it is reccomended to study the perception and evaluation of social services provided by the National Board for Children in Limon from various scientific methodologies and the with people directly involved (audiences and institutional officials).